1992
DOI: 10.3758/bf03330444
|View full text |Cite
|
Sign up to set email alerts
|

Short-term haptic memory for complex objects

Abstract: College students actively felt complex objects for 3 sec, and, after delay intervals of 5, 15, 30, or 45 sec, they received either the same object or a different object for comparison. In a signal detection framework, it was observed that d' scores were significantly higher for the 5-and 15sec intervals than for the 30-and 45-sec intervals. Although a clearly negatively accelerated function was not obtained, this is one of the rare instances in which any decay function has been observed for haptic memory. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 7 publications
4
16
1
Order By: Relevance
“…More interesting, we found that in each modality, there was no effect of interstimulus delay on objects that were more discriminable than on objects that changed on either the x-or y-axis only (Experiment 2). We suggest that interstimulus similarity may affect performance over different delays and that this may explain the inconsistencies in the literature between effects of delay on cross-modal recognition tasks (Garvill & Molander, 1973;Kiphart et al, 1992). Spatial differences, however, interacted with interstimulus intervals in our within-modal experiment only (Experiment 2) and not in our cross-modal experiment (Experiment 1), although changes in xy resulted in better performance in both experiments.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…More interesting, we found that in each modality, there was no effect of interstimulus delay on objects that were more discriminable than on objects that changed on either the x-or y-axis only (Experiment 2). We suggest that interstimulus similarity may affect performance over different delays and that this may explain the inconsistencies in the literature between effects of delay on cross-modal recognition tasks (Garvill & Molander, 1973;Kiphart et al, 1992). Spatial differences, however, interacted with interstimulus intervals in our within-modal experiment only (Experiment 2) and not in our cross-modal experiment (Experiment 1), although changes in xy resulted in better performance in both experiments.…”
Section: Discussioncontrasting
confidence: 47%
“…The tone lasted for 3 sec and on offset, the participants had to remove their hands from the object. Thus, haptic exploration of an object lasted for 3 sec, which was considered adequate time to encode the properties of the object through touch (Kiphart et al, 1992). A visual presentation of a stimulus was preceded by a fixation cross for 500 msec, which alerted the participant and prepared him or her for the subsequent presentation of a visual stimulus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the haptic condition in Experiment 1 took around 30 min to complete-15 min per block-so perceptual information had to be retained over several minutes. There is evidence that haptic memory of objects alters over time, with some findings suggesting that it decays rapidly, over several seconds (e.g., Kiphart, Hughes, Simmons, & Cross, 1992), but other research suggesting that haptic discrimination and matching may improve over time (Norman, Clayton, Norman, & Crabtree, 2008;Zuidhoek, Kappers, van der Lubbe, & Postma, 2003). The significant recognition advantage when the standard exemplars were presented twice in Experiment 1 demonstrates that durable representations were encoded, but size changes might impair performance more on a short-term matching task than on a longer-term recognition task.…”
Section: Materials and Apparatusmentioning
confidence: 99%
“…Other studies report that tactile memory can be sustained for 15 sec (Kiphart, Hughes, Simmons & Cross, 1992) and is vulnerable to articulatory suppression (Mahrer & Miles, 2002). However, performance can also be affected by the task demands or stimulus complexity and the degree of familiarity with the objects being explored (Millar 1981 Newell (2004) suggested that tactile-visual object recognition may rely on modality specific representations.…”
Section: Vision-visionmentioning
confidence: 99%